Evaluasi Pelayanan Penumpang Bandara Mutiara Palu - Ari Susetyadi (WARTA ARDHIA, 2010)
The airport is an for aviation services, where in variety of good facilities for service to the aircraft as well as for passanger service. Air transport passenger service at airport from time to time require upgrading the performance of services, both from land and air side services. Which became problems as Palu Mutiara airport if the airport is already providing service accordance with the standard of service (level of sercvice). and how the airport in activities of air transport services with limited passenger terminal condition, especially during busy (peak season).